2006
DOI: 10.1016/j.pain.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice for acute low back pain in primary care: Patient outcomes and cost of care

Abstract: Provider adherence with clinical practice guidelines (CPGs) for acute low back pain (LBP) and its impact on clinical outcomes and cost are controversial. A panel and cross-sectional design was used to determine the rate of provider adherence to the Department of Defense/Veteran's Administration CPG for Acute LBP which included ergonomic and psychosocial intervention. The relationship among adherent care, patient satisfaction, general health, functional outcome, and cost was examined. Direct health services and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 25 publications
1
56
0
1
Order By: Relevance
“…Growing evidence exists to support a multidisciplinary therapeutic approach, and physicians should follow clinical practice guidelines in their daily management of LBP 2,3,20 . The integral role played by psychological and social factors in LBP is still largely ignored; attention to it is reserved for patients who do not respond to cheaper treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence exists to support a multidisciplinary therapeutic approach, and physicians should follow clinical practice guidelines in their daily management of LBP 2,3,20 . The integral role played by psychological and social factors in LBP is still largely ignored; attention to it is reserved for patients who do not respond to cheaper treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (LBP) is a common public health problem world-wide [1][2][3] . For quite a number of patients affected by the development of chronic back pain, the disease is extremely disabling; it is likely to show co-morbidity with mood disorders and is associated with serious risk of ending in early retirement or an inability to cope with activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Yet there is a strong body of evidence suggesting a low level of adherence to guidelines in daily clinical practice. 43,44 Overall adherence to guideline-based care by PCPs has been recorded at 65%, a rate that has remained unchanged despite attempts to increase implementation of evidence-based care.…”
Section: Current Clinical Practicesmentioning
confidence: 99%
“…This situation appears to be widespread and common to other health care professionals; unfortunately, studies have found that many guidelines are not used after their development and dissemination, [15][16][17] despite the fact that adherent care has been shown to produce better clinical outcomes and lower costs. 18,19 Research on implementation strategies to improve adherence to guidelines has shown the value of education, discussion, role-playing, feedback, and reminders. 20,21 However, these implementation strategies frequently produce only moderate improvement.…”
Section: Awareness Of Cpgsmentioning
confidence: 99%